Self-Propelled Motion of the Camphor Float With n-Fold Rotational Symmetry - Kitahata, Hiroyuki; Koyano, Yuki (Frontiers in Physics, 2022)
It is known that a camphor particle at a water surface exhibits self-propulsion since it releases camphor molecules at the surface and reduces the surface tension, and the gradient of surface tension drives the camphor particle itself. Such a motion is considered to be driven by the concentration field of the chemicals emitted by the particle itself. It is also known that the shape of the particle seriously affects the mode of motion. In order to understand the universal mechanism on the effect of the shape on such a self-propelled motion, we theoretically investigated the bifurcation structure of the motion of the camphor float with n-fold rotational symmetry, which comprises n camphor disks attached to a rigid light circular plate along a periphery with an equivalent spacing. Here, we mainly studied the cases with n=2 and 3. We found that the camphor float with n=2 moves in the direction perpendicular to the line connecting the two camphor disks, while that with n=3 changes its direction of motion depending on the size of the camphor float.